Nationality and Rationality: Ancestors, ‘Diaspora’ and the Impact of Ethnic Policy in the Country of Emigration on Ethnic Return Migration from Western Ukraine to the Czech Republic - Luděk Jirka (Central and Eastern European Migration Review, 2019)
Ethnic return migration is a widespread strategy for migrants from economically disadvantaged countries. This article is about those ethnic return migrants who might successfully migrate thanks to their ancestors; their decision is based upon economic, pragmatic or rationalistic incentives aside from their diasporic feeling of belonging. Although this phenomenon has already been studied, scholars still mostly refer only to the benefits proposed by immigration policy as a key to understanding it. The impact of policy in the country of emigration on ethnic return migration is understudied. This article fills this gap. I found that when the Soviet Union introduced an attractive policy for Ukrainians/Russians in terms of study or work opportunities and the inhabitants in the Ukrainian Soviet Republic were quick to proclaim themselves as Ukrainians or Russians, the dissolution of the Soviet Union quickly changed this motivation. Ukrainians with Czech ancestors started to aim at obtaining official status as Czech members of the diaspora because of the benefits proposed by the Czech government (mainly permanent residency). However, it is difficult to prove the required link to one’s Czech ancestors due to Soviet-era documents in which the column with the Czech nationality of people’s ancestors is often missing. These observations lead to the conclusion that an attractive immigration policy aimed at the diaspora should not be treated as the only comprehensive explanation for ethnic return migration. Ethnic policy in the country of emigration also shapes this kind of migration and – in this concrete case – could even discourage ethnic return migrants.